First report of Ixodes (Pholeoixodes) hexagonus on chukar (Alectores chukar) in Northwest of Iran and it’s public health importance - Mousa Tavassoli; Ehsan Mohamadi (Persian Journal of Acarology)
Ixodid ticks are obligatory blood-sucking ectoparasites of various mammals, birds, reptiles and vectors of different agents of diseases in both man and livestock. Ixodes hexagonus was reported from different parts of the globe and it is important as a vector of different diseases such as Lyme disease. A total of 53 chukars were sampled. The birds were obtained from hunters or dealers on different occasions from several localities across the south of Urmia city, West Azerbaijan of Iran. In this study, we report infestation of I. hexagonus in chukar and it is the first report of I. hexagonus from Iran. The results indicated that 28 chukars were infected by ticks. Considering that the I. hexagonus is one of the major vectors of Borrelia burgdorferi, Babesia microti and Rickettsia conori, the report of this tick in this region could mean more disease transmission. More attention should be given to the search of this parasite in similar geographical regions in Iran. Additionally, molecular work should be done to show the importance of I. hexagonus tick in the transmission of different diseases especially Lyme borreliosis.